Incidence of microplastics in gastrointestinal tract of golden anchovy (Coilia dussumieri) from north east coast of Arabian Sea: The ecological perspective. (August 2021) - Gurjar, Udai Ram; Xavier, K.A. Martin; Shukla, Satya Prakash; Deshmukhe, Geetanjali; Jaiswar, Ashok Kumar; Nayak, Binaya Bhusan
Abstract: Anthropogenic marine litters or microplastics (MPs) accumulation in marine organisms is an emerging environmental threat. In this background, the gastrointestinal tract of Coilia dussumieri ( n  = 150) was studied in the samples collected from the fishing grounds of the north east coast of Arabian Sea through experimental fishing. Out of the total 150 specimens collected, all showed the incidence of microplastic particulates in the guts. The average abundance of MPs was found to be 6.98 ± 2.73 items/individual whereas gastrointestinal tract recorded with an average number of 28.84 ± 10.13 MPs/g in the gut material. The dominant MPs were found in the size range of 100–250 μm and of fibers type mostly blue in color. The prevalence of MPs in Coilia dussumieri is a matter of serious concern due to its ecological consequences due to trophic transfer in the connected food chains and probable threats to the health of human beings consuming the fish. Highlights: Microplastics in aquatic organisms are serious concern due to ecological consequences. The study proven the incidence of MPs at field level from the north eastern Arabian Sea. An average 6.98 ± 2.73 MPs per individual was observed with dominance of fiber. The MPs with size range 100–250 μm were the most dominant. MPs contamination can create health risk to the humans, due to chance of trophic transfer.